Genome-wide identification of oat TCP gene family and expression patterns under abiotic stress - Nie, Jiaming; Zhao, Hongbin; Guo, Xiaodong; Zhang, Tao; Han, Bing; Liu, Huiyan (Frontiers in Genetics, 2025)
TCP transcription factors are a unique class of transcription factors that play important roles in alleviating abiotic stresses such as drought and salt. In this study, the whole-genome data of three cultivated varieties, namely, “SFS”, “Sang” and “OT3098v2”, were utilized to identify and analyze the members of the TCP gene family in oats, and their responses to two abiotic stresses, drought and salt, were also investigated. Results showed that there are 83, 65, and 30 non-redundant TCP genes in the three oats, with the highest number of TCP genes specific to the “SFS”, reaching 22 genes. The oat TCP genes can be classified into three subfamilies: PCF, CIN, and CYC/TB1. Most AsTCP genes have important motifs, Motif 1 and Motif 2, which are part of the bHLH domain. Additionally, various cis-acting elements related to hormone response, abiotic stress, light response, and growth and development were found in the promoters of AsTCP genes. The main amplification mechanism of the oat TCP gene family is fragment duplication. Two tandem duplications, AsTCP058/AsTCP059 and AsTCP023/AsTCP025, are stably present in the three oats. The highest number of AsTCP collinear relationships exist in the “SFS” with 89 pairs. After drought and salt stress treatments, significant differences in gene expression were observed among different oat cultivars and treatment periods. Genes that showed significant expression changes under both treatments (AsTCP021, AsTCP033, AsTCP044, AsTCP053, and AsTCP058) may play important roles in oat’s response to abiotic stresses. Notably, AsTCP053 gene was significantly upregulated at 24 h of stress treatment and showed a more sensitive response to salt stress. This study provides insights into the functional characterization of the oat TCP gene family and its molecular mechanisms underlying stress tolerance.